Determinants of Optimizing the Role of Bhabinkamtibmas in Building Public Trust - M. Awal Chairuddin; Husain Syam; Haedar Akib; Toto Imam Santoso; Hasnawi Haris; Rifdan Rifdan (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
Determinants as supporters or obstacles to optimizing the role of Bhabinkamtibmas in building public trust are analogous to two sides of one coin which revolves around the implementation of the main tasks, authority, and functions of the institution that accommodate it. These organizational factors have a sustainable impact on service effectiveness and strengthening relations between government institutions and the community. The article resulting from this research explains the determinants of optimizing the role of Bhabinkamtibmas in building public trust in certain loci. Data, information, and knowledge regarding the research focus were obtained through observations, interviews, and focus group discussions with informants as members of Bhabinkamtibmas (police, army, sub-district officials), community leaders, religious leaders, non-governmental organizations (NGOs), and academics. The data is analyzed using an interactive model which includes data collection, data condensation, and verification using the Important Performance Analysis (IPA) technique which is presented through a spider curve, and drawing conclusions. The research results found that there are several aspects as determinants that support or hinder efforts to build public trust in the demarcation of duties of the Makassar Indonesian Big City Resort Police (Polrestabes). Determinants as supporters or obstacles to optimizing the role of Bhabinkamtibmas in building public trust include the quality of public services, actor leadership style, transparency and accountability, public participation, effective communication, justice and equality in public policies and services, competency and integrity of the apparatus. The glue that unites the sustainability of these determinants is the leadership style and learning of the Bhabinkamtibmas organization as a representation of the Indonesian National Police (Polri).